If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2(2 + -2x) = 2x + 9 x + (2 * -2 + -2x * -2) = 2x + 9 x + (-4 + 4x) = 2x + 9 Reorder the terms: -4 + x + 4x = 2x + 9 Combine like terms: x + 4x = 5x -4 + 5x = 2x + 9 Reorder the terms: -4 + 5x = 9 + 2x Solving -4 + 5x = 9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 5x + -2x = 9 + 2x + -2x Combine like terms: 5x + -2x = 3x -4 + 3x = 9 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 3x = 9 + 0 -4 + 3x = 9 Add '4' to each side of the equation. -4 + 4 + 3x = 9 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 9 + 4 3x = 9 + 4 Combine like terms: 9 + 4 = 13 3x = 13 Divide each side by '3'. x = 4.333333333 Simplifying x = 4.333333333
| -2(x+1)=-2x-2 | | 15/2x=3/5+x | | -7(z-5)=-8z | | 2n+12=1 | | 2a^3+162a=0 | | X/6=20 | | 3x+4=4(x+8) | | -(4z-(10z+1))=1+(5z+2) | | 25s^2-10sd+d^2= | | 4.5x-12=24 | | 4g=3 | | -9=12+x | | 24/y-x | | -9=-x-8x | | 2(x+5)+2(x-3)=(x+2)+(3x-11)+(3x-11) | | 2z+4z=5z-1 | | 9/11x-1/11 | | 6(v+8)=-5(2v-8)+4v | | 27=12-2(x+2) | | 3(2y+4)=5(3y+6) | | 2(-4+2p)+3p=-5+4p | | -4d+2(3+d)=-1 | | 2(k-(2k+7)+6)=2(k+1) | | logx+(x+6)=2 | | 4x/5+6x/10=-12 | | m+5/12 | | 7-3(1-4p)=76 | | 6(-3x+4)=-10x+8 | | 6(9+x)=5(9+x) | | 9(4c-1)-12=34c+9 | | 5/3+10/3y=3y-2 | | X+3v=24 |